2021
DOI: 10.1007/s00217-021-03707-z
|View full text |Cite
|
Sign up to set email alerts
|

Odour-active compounds in liquid malt extracts for the baking industry

Abstract: An odorant screening by gas chromatography–olfactometry (GC–O) and a crude aroma extract dilution analysis (AEDA) applied to the volatiles isolated from a light and a dark liquid malt extract (LME) by solvent extraction and solvent-assisted flavour evaporation (SAFE) identified 28 odorants. Fifteen major odorants were subsequently quantitated and odour activity values (OAVs) were calculated as ratio of the concentration to the respective odour threshold value (OTV). Important odorants in the light LME included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 67 publications
1
35
0
Order By: Relevance
“…Water was added to the powdered crust and crumb samples before solvent extraction to consider the release of bound odorants by saliva during bread consumption. Particularly in foods with low moisture content such as malt, oat products, and also bread crust, a considerable increase of the odorant concentrations after water addition has previously been observed. ,− We recently showed that the concentrations of phenylacetaldehyde, phenylacetic acid, and vanillin in malt increased 9–33-fold after water addition. Furthermore, we demonstrated that the addition of a minor amount of water together with the extraction solvent is sufficient to achieve an exhaustive release of the bound odorants .…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Water was added to the powdered crust and crumb samples before solvent extraction to consider the release of bound odorants by saliva during bread consumption. Particularly in foods with low moisture content such as malt, oat products, and also bread crust, a considerable increase of the odorant concentrations after water addition has previously been observed. ,− We recently showed that the concentrations of phenylacetaldehyde, phenylacetic acid, and vanillin in malt increased 9–33-fold after water addition. Furthermore, we demonstrated that the addition of a minor amount of water together with the extraction solvent is sufficient to achieve an exhaustive release of the bound odorants .…”
Section: Resultsmentioning
confidence: 91%
“…The following isotopically substituted odorants were purchased from commercial sources: ( 13 C 2 )- 36 (aromaLAB, Martinsried, Germany), ( 2 H 11 )- 5a , ( 2 H 7 )- 17 , ( 2 H 5 )- 31 (CDN Isotopes, Quebec, Canada), ( 2 H 3 )- 11 , and ( 13 C 2 )- 47 (Merck, Darmstadt, Germany). Compounds ( 13 C 5 )- 7 , ( 2 H 3 )- 12 , ( 2 H 2 )- 14 , ( 2 H 2 )- 20 , ( 13 C 2 )- 21 , ( 2 H 2 )- 22a , ( 2 H 4 )- 25 , ( 2 H 6 )- 27 , ( 2 H 3 )- 29 , ( 13 C 2 )- 33 , ( 13 C 6 )- 41 , ( 13 C 2 )- 42 , ( 2 H 3 )- 43 , and ( 2 H 3 )- 48 were synthesized as detailed in the literature. ( 13 C 2 )- 26 was prepared according to the approach published by Kiefl et al .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It allows the analysis of not only the aroma compounds themselves, but also their individual impact to the overall composition of the products by means of aroma extract dilution analysis (AEDA). Just recently, Rögner, Mall, and Steinhaus (2021) applied SAFE for the extraction of aroma compounds of malt, aiming to identify key aromas in light and dark liquid malt extracts for the baking industry. Furthermore, the authors compared the concentrations found in the liquid extracts to those in the respective malt, realizing that the formation of the aroma compounds during the liquid extract production is more important than their direct transfer from the malt.…”
Section: Aroma‐active Compounds Of Specialty Malts and Sensory Analysismentioning
confidence: 99%